2021
DOI: 10.3390/cimb43030123
|View full text |Cite
|
Sign up to set email alerts
|

Geraniol Averts Methotrexate-Induced Acute Kidney Injury via Keap1/Nrf2/HO-1 and MAPK/NF-κB Pathways

Abstract: Objectives: Geraniol, a natural monoterpene, is an essential oil component of many plants. Methotrexate is an anti-metabolite drug, used for cancer and autoimmune conditions; however, clinical uses of methotrexate are limited by its concomitant renal injury. This study investigated the efficacy of geraniol to prevent methotrexate-induced acute kidney injury and via scrutinizing the Keap1/Nrf2/HO-1, P38MAPK/NF-κB and Bax/Bcl2/caspase-3 and -9 pathways. Methods: Male Wister rats were allocated into five groups: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 44 publications
9
11
1
Order By: Relevance
“…In the present study, MTX-induced nephrotoxicity was associated with disturbed renal function tests, elevated serum creatinine, and urea, and with induction of apoptosis as noticed through upregulation of the apoptosis marker BAX and downregulation of the anti-apoptosis marker BCL-2. We also determined that MTX could induce an inflammatory response, as seen through activation NF-kappaB, similar to the findings of Younis et al [ 32 ] who reported the cytotoxic effect of MTX, causing cell death. In addition, MTX caused renal oxidative stress as marked by increased renal MDA, NO, and decreased renal GSH, consistent with the previous reports [ 29 ].…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, MTX-induced nephrotoxicity was associated with disturbed renal function tests, elevated serum creatinine, and urea, and with induction of apoptosis as noticed through upregulation of the apoptosis marker BAX and downregulation of the anti-apoptosis marker BCL-2. We also determined that MTX could induce an inflammatory response, as seen through activation NF-kappaB, similar to the findings of Younis et al [ 32 ] who reported the cytotoxic effect of MTX, causing cell death. In addition, MTX caused renal oxidative stress as marked by increased renal MDA, NO, and decreased renal GSH, consistent with the previous reports [ 29 ].…”
Section: Discussionsupporting
confidence: 88%
“…The BCL-2 family of intracellular proteins are considered key regulators of apoptosis [36] . In the current study, increased ROS and inflammation were associated with oxidative DNA damage and upregulated Bax and Caspases [37] . NRF2 confers resistance to apoptosis by inducing expression of ROS-scavenging enzymes and BCL-2 family members, such as Bcl-2 and Bcl-xl [38] .…”
Section: Discussionsupporting
confidence: 52%
“…Although exposure to moderate OS can lead to Nrf2 activation, the excessive and sustained ROS generation can diminish Nrf2 signaling in the kidney and liver of rats challenged with MTX; thus, the diminished Nrf2/HO-1 pathway is a direct consequence of the sustained ROS generation induced by MTX (31) .…”
Section: Discussionmentioning
confidence: 99%